Impact of Pharmacist Intervention in Response to Automated Molecular Diagnostic Tests of Blood Culture Results. (February 2022) - McCarthy, Lauren; Colley, Peter; Nguyen, Hoa L.; Berhe, Mezgebe
Background: Rapid molecular diagnostic tests can aid in deescalating antimicrobial therapy prior to final culture and susceptibility reports. Objective: The purpose of this study was to determine whether a new workflow that incorporated pharmacist review of these results reduced time to change in antimicrobial therapy. Methods: This retrospective study analyzed pre- and post-implementation of pharmacist review of positive blood cultures analyzed by rapid diagnostics with clinical recommendations paged to providers. Patients 18 years of age or older initiated on empiric antibiotics were included. The primary outcome was the time to change to targeted antimicrobials. Other outcomes evaluated were rates of Clostridioides difficile (C difficile) infection, inpatient mortality, and intensive care unit and hospital lengths of stay. Results: A total of 199 patients were included, with 98 and 101 patients in the pre- and post-implementation groups, respectively. The median time to change to targeted antimicrobials was significantly reduced with pharmacist intervention from 18.35 to 8.43 hours ( P = 0.042). The groups had similar rates of C difficile infection (1% vs 0%, P = 0.492) and mortality (7.1% vs 5%, P = 0.564). The post-group also had significant reductions in antibiotic days of therapy (10.5 vs 9 days, P = 0.014) and intensive care unit length of stay (3.04 vs 1.44 days, P = 0.046). Median hospital length of stay was similar between the pre- and post-groups (8.5 vs 8 days, P = 0.106), respectively. Conclusion: Incorporating pharmacist review of rapid molecular results of blood cultures decreased time to change to targeted antimicrobials and reduced inpatient antibiotic days of therapy.